Analisis Persepsi Masyarakat terhadap Pengelolaan Kawasan Mangrove Teluk Kotania - Hellen Nanlohy; Azis Nur Bambang; Ambaryanto Ambaryanto; Sahala Hutabarat (Department of Urban and Regional Planning, Diponegoro University, 2014)
Coastal development is growing rapidly due to high population growth. This condition will threaten the sustainability of the region and coastal ecosystems.The goal of this research is to analyze the perception of communities towards sustainable coastal management. This research used survey method with case study. The research was conducted in the five villages in Teluk Kotania. Techniques of data collection using interviews, observation, and secondary data. Data analyzed by qualitative description with average score and distance scale. The analysis shows that coastal communities in Teluk Kotania are very agree for 1) region mangrove management order that preserve; 2) people’s participation were very important to region mangrove management; and then 3) Government and coastal people’s must be work together to region mangrove management.